Pre‐symptomatic transmission of novel coronavirus in community settings. Issue 6 (19th June 2020) - Kong, Dechuan; Zheng, Yang; Wu, Huanyu; Pan, Hao; Wagner, Abram L.; Zheng, Yaxu; Gong, Xiaohuan; Zhu, Yiyi; Jin, Bihong; Xiao, Wenjia; Mao, Shenghua; Lin, Sheng; et al.
Abstract: We used contact tracing to document how COVID‐19 was transmitted across 5 generations involving 10 cases, starting with an individual who became ill on January 27. We calculated the incubation period of the cases as the interval between infection and development of symptoms. The median incubation period was 6.0 days (interquartile range, 3.5‐9.5 days). The last two generations were infected in public places, 3 and 4 days prior to the onset of illness in their infectors. Both had certain underlying conditions and comorbidity. Further identification of how individuals transmit prior to being symptomatic will have important consequences.